(3GdCfhGQ GdSfjI Yf GdhXjaI GdRQhbjIs - (3YHO GdQMef Hf eMeO Hf YHO GdQMef Hf eMeO fH CHi HcQ GdYjGTis
(3ChdgG (B:s
(3hHYO ajbhd bO WGd eG NGdL bdHi Cf CVY JbjjOkG jchf cGdTQM Ydi GdhXjaI GdRQhbjI efWhjkG Ydi JaSjQ ZQGFHgG , heMJhjkG Ydi aVjdI CPcGQgG hSejJg hCbOe ChdkG GdJYQja HGdeDda s
(3BNQgG (B:s
(3hbGd QShd Gddg hGdPi HYKfi HGdMb HTjQkG hfPjQkG dbO RGMeJfi GdedGFcI eG bOQJ Cf CUdi Ydjg ZdG efMQakG Gddge jG ef bVi Ydjg HGdLfI GbV dfG HgG HLGg eMeO Udi Gddg JYGdi Ydjg s
(3GdfSNI HgG MhGTs
(3fSNI eUMMIs
(3HYV YHGQGJgG HGdMeQI s
(3hHgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdeYGQa GdYGeIs